Media Pembelajaran Vidio dalam Pembelajaran Sejarah: Studi Kasus di SMA Sejahtera 1 Depok - Yusuf Budi Prasetya Santosa; Hendi Irawan; Fahmi Hidayat (LITERATUS, 2021)
Learning media is one of the important components in the learning process. For teachers, the use of learning media can help in delivering the subject matter. As for students, learning media can help understand the learning material. One of the learning media used by teachers is learning video media. Learning video media can provide a concrete picture of the ideas and ideas contained in the subject matter. The subject is one of the subjects that are suitable for using learning videos. This study aims to see how the use of learning media and how to apply instructional video media in learning history. The population and sample of the entire study were students of class XI IPS at SMA Sejahtera 1 Depok. results Based on the research that has been done, video learning media is a good medium to use in history subjects. Learning video media can also increase the effectiveness and enthusiasm of students' learning.